2020
DOI: 10.3390/cancers12071825
|View full text |Cite
|
Sign up to set email alerts
|

Unique Spatial Immune Profiling in Pancreatic Ductal Adenocarcinoma with Enrichment of Exhausted and Senescent T Cells and Diffused CD47-SIRPα Expression

Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is resistant to single-agent immunotherapies. To understand the mechanisms leading to the poor response to this treatment, a better understanding of the PDAC immune landscape is required. The present work aims to study the immune profile in PDAC in relationship to spatial heterogeneity of the tissue microenvironment (TME) in intact tissues. Methods: Serial section and multiplex in situ analysis were performed in 42 PDAC samples to assess gene and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Tolerance is exacerbated by TGF-β and IL-10 [ 18 ]. Taken together, senescent, anergic and exhausted T c cells often co-exist in the TME or circulation and simultaneously exert immunosuppressive effects [ 11 , 19 ]. The current limitations of check-point inhibitors suggest that targeting multiple dysfunctional T c cell states would be therapeutically beneficial.…”
Section: Exhaustion and Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…Tolerance is exacerbated by TGF-β and IL-10 [ 18 ]. Taken together, senescent, anergic and exhausted T c cells often co-exist in the TME or circulation and simultaneously exert immunosuppressive effects [ 11 , 19 ]. The current limitations of check-point inhibitors suggest that targeting multiple dysfunctional T c cell states would be therapeutically beneficial.…”
Section: Exhaustion and Senescencementioning
confidence: 99%
“…Senescent T cells have been found in primary and metastatic solid tumor sites [ 19 , 20 , 21 , 22 , 23 ] as well as hematological malignancies [ 11 , 24 ]. T c senescence can be classified into two major cellular mechanisms which are however not entirely separated from one another: premature and replicative senescence.…”
Section: Mechanisms Of T Cell Senescence Inductionmentioning
confidence: 99%
“…Interestingly, the present study showed that PD‐L1 expression was significantly associated with SIRPα expression in ESCC. Previous studies showed that PD‐L1 is expressed in TAMs and plays a role in regulating their phagocytosis 41‐43 . Our IHC analysis suggested that SIRPα could be expressed in TAMs.…”
Section: Discussionmentioning
confidence: 49%
“…This may be related to the Th1 cells among CD4 + T cells that activate CD8 + CTLs and promote the immune system to suppress tumor progression ( 5 ). A previous study explored the spatial distribution and functional status of T cells in different areas, including the tumor center, invasive front, normal parenchyma adjacent to the tumor, and tumor-positive and tumor-negative draining lymph nodes in PDAC ( 32 ). However, the current study explored only the infiltration of T cells in the PDAC tumor region and did not explore the functional status of T cells.…”
Section: Discussionmentioning
confidence: 99%